2018
DOI: 10.1007/s11121-018-0889-2
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Promotion Online: an Investigation of Dispensary Practices

Abstract: Marijuana product advertising will become more common, as the use of medical and/or recreational marijuana becomes increasingly legal in the USA. In this study, we investigate the marketing tactics being used on marijuana dispensary websites in the USA that could influence substance use behaviors. One hundred dispensary websites were randomly selected from 10 states that allowed the legal use of medical or recreational marijuana and had at least 10 operational dispensaries. Three dispensaries were excluded due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 28 publications
4
45
0
1
Order By: Relevance
“…chemotypes/products across 653 dispensaries [27]. Therefore, our results are likely a fair representation of the potency of online products offered in dispensaries across the U.S.…”
Section: Plos Onementioning
confidence: 79%
See 2 more Smart Citations
“…chemotypes/products across 653 dispensaries [27]. Therefore, our results are likely a fair representation of the potency of online products offered in dispensaries across the U.S.…”
Section: Plos Onementioning
confidence: 79%
“…In addition, 70% of all dispensary staff reported that a lack of knowledge served as a barrier to making a medical recommendation [50]. This trend is exacerbated by the fact that less than half of dispensaries across the country advise patients of potential side effects and even fewer warn of potential contraindications, while many promote ill-supported medical benefits [27].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In states with MMLs or RMLs, the presence of dispensaries or retail outlets and how marijuana is marketed represent additional contextual factors that can influence marijuana use among adolescent and emerging adults. Cavazos-Rehg et al (2019), in this issue, examined online promotion of marijuana by randomly selecting 100 dispensaries from 10 states that had RMLs or MMLs and that also had at least 10 operational dispensaries. Their work showed that 75% of the sites for dispensaries did not require age verification to view their website and that 67% included unwarranted claims about health effects of marijuana.…”
Section: Predictors Of Marijuana Use From Multiple Ecological Domainsmentioning
confidence: 99%
“…With this special issue, we seek to advance prevention science research on marijuana use among adolescents and emerging adults. The 10 original articles in this issue describe patterns of use among young people and provide new information about associated risk and protective factors at multiple ecological levels (Brooks-Russell et al 2019;Cavazos-Rehg et al 2019;Fairman et al 2019;Guttmannova et al 2019a;Johnson et al 2019;Mauro et al 2019;Nguyen et al 2019;Reboussin et al 2019;Thompson et al 2019;Wen et al 2019). An additional commentary describes the importance of using existing data to characterize the epidemiology of marijuana use in response to state laws (Guttmannova et al 2019b).…”
Section: Introductionmentioning
confidence: 99%